Ryzyko z perspektywy badań kulturowych. Wybrane problemy metodologiczne - Burzyński, Tomasz (Er(r)go. Teoria - Literatura - Kultura, 2014)
Tomasz Burzyński Risk and Cultural Studies. Selected Methodological Dilemmas This article aims to outline theoretical and methodological frameworks that may facilitate a more informed inquiry into the nature of technological risks from the conceptual perspective of cultural studies. Despite its roots in technical and economic sciences, the notion of risk seems to fit perfectly into a plethora of culturally-oriented discourses whose common denominator is a criticism focused at scientific and technological pillars of (late) modern civilizations. When perceived in an overtly cultural context, risk functions as a discourse which embraces, on the one hand, social, political and moral consequences of modernization processes, and, on the other hand, symbolic practices which aim to construct cultural representations of diversified technological dangers.